Bäddodling av matpotatis - Kjell, Carl (2008)
This study investigated potato growing in beds as an alternative to conventional ridges.It was based on results from field trials on bed-grown potatoes carried out by Halland Rural Economy and Agricultural Society in 2007, studies of literature and interviews with farmers with experience of bed growing of potatoes.